Bacterial Extracellular DNA Production Is Associated with Outcome of Prosthetic Joint Infections. (22nd October 2018) - Zatorska, Beata; Arciola, Carla Renata; Haffner, Nicolas; Segagni Lusignani, Luigi; Presterl, Elisabeth; Diab-Elschahawi, Magda
Abstract : In a retrospective study the association of the production of extracellular DNA (eDNA) in biofilms of clinical staphylococcal isolates from 60 patients with prosthetic joint infection (PJI) and the clinical outcome were investigated. Data from a previous study on eDNA production determined in 24-hour biofilms of staphylococcal isolates (S taphylococcus aureus n=30, Staphylococcus epidermidis n=30) was correlated with the patients' clinical outcome after 3 and 12 months. Statistical analysis was performed using either the Spearman's rank correlations test or the t-test. eDNA production of S. epidermidis in 24-hour biofilms correlated with the patients' outcome 'not cured' after 12 months. For S. aureus no such correlation was detected. Thus, eDNA may be a virulence factor of S. epidermidis. Quantification of eDNA production as a surrogate marker for biofilm formation might be a potential predictive marker for the management of PJI.